Johannine writings and apocalyptic : an annotated bibliography - Porter, Stanley E., 1956- (Johannine Studies, 2013)
Johannine Writings and Apocalyptic provides a wide-ranging and thorough annotated bibliography for John's Gospel, the Johannine letters, Revelation, and apocalyptic writings pertinent to these books. More inclusive than many other bibliographies, this volume provides reference to over 1300 individual entries, often including references to multiple works with a given description. Annotations are designed to provide guidance to a wide range of readers, from students wishing to gain entry to the subject to graduate students engaging in research to professors needing ready access to useful materials. The volume is topically organized and indexed for easy access.